Acute effects of combined isometric and plyometric conditioning activities on sports performance and tendon stiffness in female volleyball players - Kalinowski, Rafał; Pisz, Anna; Kolinger, Dominik; Wilk, Michał; Stastny, Petr; Krzysztofik, Michał (Frontiers in Physiology, 2022)
This study aimed to compare the effects of combined isometric and plyometric bilateral and unilateral conditioning activities (CA) on countermovement jump performance, modified t-agility test, Achilles tendon stiffness and skin surface temperature. Thirteen female semi-professional volleyball players performed two CAs in random order: i) bilateral isometric half back squats followed by bilateral drop jumps (BI-CA); and ii) unilateral isometric half back squats followed by unilateral drop jumps (UNI-CA). To assess the effects of CAs, countermovement jump, modified t-agility test, Achilles tendon stiffness and skin surface temperature measurements were performed 5 min before and 6 min after the CA. Both CAs significantly increased thigh skin surface temperature from pre- to post-CA (BI-CA, p<0.001; effect size [ES]=1.41 and UNI-CA, p=0.001; ES=1.39) but none of them influenced modified t-agility test time (p>0.05, ES=-0.13 and p>0.05, ES=-0.27; respectively). The countermovement jump height and modified reactive strength index significantly increased from pre- to post-CA during the BI-CA condition (p=0.005, ES=0.45, and p=0.008, ES=0.48). Moreover, stronger and weaker limb relative peak force significantly decreased from pre- to post-CA (p=0.014, ES=-0.31, and p=0.027, ES=-0.26; respectively) during UNI-CA. The stronger and weaker limb Achilles tendon stiffness significantly increased from pre- to post-CA during the UNI-CA condition (p=0.013, ES=0.62 and p<0.001, ES=0.77; respectively). Furthermore, the post-CA stronger limb Achilles tendon stiffness during the UNI-CA was significantly higher than that noted during the BI-CA (p=0.006, ES=0.7). The present study showed that combined isometric and plyometric bilateral CA effectively improved the countermovement jump but did not enhance the t-agility test performance. These findings indicate that exercise combinations could effectively produce a post-activation performance enhancement effect but should replicate the following explosive task as much as possible.